Effects of strength and balance training on the mobility, fear of falling and grip strength of elderly female fallers - Prata, Melina Galetti [UNESP]; Scheicher, Marcos Eduardo [UNESP] (Elsevier, 2014)
The aim of this study was to evaluate the effects of virtual reality and strength training on the balance, fear of falling and handgrip strength of older women with a history of falls. The fear of falling, mobility and grip strength were evaluated in 11 elderly fallers (72.4 ± 5.2 years). The faller group was submitted to 12 weeks of virtual reality and muscle strength training. The results showed improvement in mobility (p = 0.0004) and in the fear of falling (p = 0.002). No significant difference was observed for hand grip strength. It can be concluded that virtual reality and muscle strength interventions are beneficial for mobility and fear of falling in older women with a history of falls.